Advances in high pressure bioscience and biotechnology: proceedings of the International Conference on High Pressure Bioscience and Biotechnology, Heidelberg, August 30 - September 3, 1998 - Ludwig, Horst 1937- (Springer, 1999)
At present, there is growing interest in high pressure bioscience and biotechnology. The activities are nearly equally distributed between fundamental research and applications. With original work on marine and terrestrial microbiology, biochemicstry, molecular biology, deep-sea diving, food science and other industrial applications, this book covers the whole range of current high pressure bioscience. "Advances in High Pressure Bioscience and Biotechnology" will be welcomed by all industrial and academic researchers who are working in this field
Keywords: Konferenzschrift -- 1998 -- Heidelberg; Hochdruck; Hydrostatischer Druck; Biologisches System; Biotechnologie; Lebensmitteltechnologie